The Modular Adaptor Protein Autosomal Recessive Hypercholesterolemia (ARH) Promotes Low Density Lipoprotein Receptor Clustering into Clathrin-coated Pits - Garuti, Rita; Jones, Christopher; Li, Wei-Ping; Michaely, Peter; Herz, Joachim; Gerard, Robert D.; Cohen, Jonathan C.; Hobbs, Helen H. (The Journal of biological chemistry, 2005)
Autosomal recessive hypercholesterolemia is characterized by a cell type-specific defect in low density lipoprotein receptor (LDLR) endocytosis. LDLR-mediated uptake of LDL is impaired in the liver, but not in fibroblasts of subjects with this disorder. The disease is caused by mutations in ARH, which encodes a putative adaptor protein that interacts with the cytoplasmic tail of the LDLR, phospholipids, and two components of the clathrin endocytic machinery, clathrin and adaptor protein-2 (AP-2) in vitro. To determine the physiological relevance of these interactions, we examined the effect of mutations in the ARH on LDLR location and function in polarized hepatocytes (WIF-B). The integrity of the FDNPVY sequence in the LDLR cytoplasmic tail was required for ARH-associated LDLR clustering into clathrin-coated pits. The phosphotyrosine binding domain of ARH plus either the clathrin box or the AP-2 binding region were required for both clustering and internalization of the LDLR. Parallel studies performed in vivo with the same recombinant forms of ARH in livers of Arh-/- mice confirmed the relevance of the cell culture findings. These results demonstrate that ARH must bind the LDLR tail and either clathrin or AP-2 to promote receptor clustering and internalization of LDL.